Penerapan Model Pembelajaran STEAM dalam Meningkatkan Kompetensi Siswa Sekolah Dasar - Nonik Safitri; Ari Suriani (Lembaga Pengembangan Kinerja Dosen, 2025)
The low ability of elementary school students to understand and connect interdisciplinary concepts highlights the need for an integrative and contextual learning approach. The STEAM (Science, Technology, Engineering, Arts, Mathematics) learning model offers a relevant alternative by fostering critical, creative, and collaborative competencies. This article aims to conceptually examine the implementation of STEAM in thematic learning within Indonesian elementary schools and to identify its potential and challenges. The analysis is based on a review of literature from various relevant sources discussing STEAM in primary education. The findings indicate that the STEAM model contributes to the enhancement of students' cognitive, affective, and psychomotor competencies, while supporting the development of 21st-century skills. This article recommends teacher training and the development of contextual learning tools to ensure the effective implementation of STEAM at the elementary level.